SISTEM INFORMASI PANDUAN TRAYEK ANGKUTAN UMUM BERBASIS MOBILE SMARTPHONE PADA DINAS PERHUBUNGAN JAKARTA - Prabowo, Heri; Herlawati, Herlawati; Mustika, Wida Prima (Jurnal Pilar Nusa Mandiri, 2014)
Public transport is an integral part of the city's transportation system and is a component whose role is very significant because the condition of the poor public transport system will cause a decline in the effectiveness and efficiency of public transport itself. Smartphone users or the public can use and take advantage of its mobile devices to be able to search for information about public transportation route and location of the place to be searched. Mobile applications natively public transportation route system is based on the PhoneGap framework and uses GoogleMaps as an interface map, the language he uses is HTML5, Javascript, JQuery Mobile. Algorithm method used is the Dijstra method. Dijkstra method can be used to determine the fastest path from a node. These properties can be applied to determine the trajectory path of nearby public transportation. The accuracy of the reading position ( Location Base Services ) on the map approximately 97 % of the radius of a meter scale map. The accuracy depends on GPS devices and mobile handsets speed internet bandwidth.